2015
DOI: 10.15825/1995-1191-2015-2-37-44
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Three-Dimensional Nanostructure of Porous Biocompatible Scaffolds Made of Recombinant Spidroin and Silk Fibroin for Regenerative Medicine

Abstract: Aim.To perform a comparison of three-dimensional nanostructure of porous biocompatible scaffolds made of fibroinBombix moriand recombinant spidroin rS1/9.Materials and methods.Three-dimensional porous scaffolds were produced by salt leaching technique. The comparison of biological characteristics of the scaffolds shows that adhesion and proliferation of mouse fibroblastsin vitroon these two types of scaffolds do not differ significantly. Comparative experimentsin vivoshow that regeneration of bone tissue of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…For the bone implants, Roentgen and CT studies revealed that after four weeks a higher recovery took place in case of rS1/9 in terms of bone formation and maturation. [61b] Further, scanning probe nanotomography confirmed a better regeneration of bone tissue in rats using rS1/9 compared to B. mori fibroin, probably due to higher nanoporosity thereof …”
Section: Regenerative Medicinementioning
confidence: 92%
See 1 more Smart Citation
“…For the bone implants, Roentgen and CT studies revealed that after four weeks a higher recovery took place in case of rS1/9 in terms of bone formation and maturation. [61b] Further, scanning probe nanotomography confirmed a better regeneration of bone tissue in rats using rS1/9 compared to B. mori fibroin, probably due to higher nanoporosity thereof …”
Section: Regenerative Medicinementioning
confidence: 92%
“…[61a] Moisenovich et al showed 3T3 fibroblasts attached and proliferated in rS1/9 scaffolds, whereby a homogeneous cell distribution throughout the material was obtained after 14 d as found by CLSM. [49,61b] Further, rS1/9 foams were compared to B. mori silk fibroin ones, which showed a similar result in terms of 3T3 fibroblast attachment and proliferation,[61b,104] but allowed a 5× faster migration through the network, leading to the conclusion that rS1/9 foams yielded a reduced motility of 3T3 cells. [61b] Freeze‐dried L‐RGDSx2 fibroin (LRF) scaffolds with a mean pore diameter of 80 µm showed promising results for bone and cartilage tissue engineering, where primary chondrocytes from white rabbits produced more cartilage‐like tissue on the surface of LRF than on native fibroin.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…Методы получения пористых клеточных мак-роносителей на основе регенерированного шелка при помощи выщелачивания с использованием в качестве порообразователя частиц хлорида натрия описаны в [20,34]. Форма и размеры использован-ных макроносителей: цилиндры с диаметром от 10 до 12 мм, высотой от 2 до 3 мм, размер макропор: от 50 до 600 мкм.…”
Section: Three-dimensional Analysis Of Micro-and Nanostructure Of Biounclassified
“…Для модификации поверхности образец порис-того макроносителя на основе регенерированного шелка [20,34] был предварительно дегазирован в эксикаторе до полного удаления из него воздуха и затем перенесен в пластиковую чашку Петри. На поверхность образца макроносителя была нанесе-на суспензия микрочастиц межклеточного матрикса децеллюляризованной печени крысы породы Wistar с концентрацией 20 мг/мл.…”
Section: материалы и методы модификация поверхности пористого клеточнunclassified
“…One type of natural material is silk fibroin (SF), which is obtained from Bombyx mori silk fibers [ 7 , 8 ]. In experiments in vitro and in vivo , SF demonstrates a high ability for adhesion, proliferation, and differentiation of stem cells [ 9 ], it is used to stimulate tissue regeneration [ 10 - 12 ], has low immunogenicity and antigenicity [ 13 ], and does not require stringent conditions for the production of biological matrices [ 14 ].…”
Section: Introductionmentioning
confidence: 99%